UJI EFEKTIVITAS PEMBERIAN MINYAK KEMIRI (Aleurites moluccanus) PADA PAKAN KOMERSIAL TERHADAP TINGKAT KONVERSI PAKAN DAN EFISIENSI PAKAN IKAN BILEH (Rasbora sp.) - Islama, Dini; Diana, Farah; Yunanda, Sry; Saputra, Fazril; Febrina, Citra Dina; Zulfadhli, Zulfadhli (Universitas Teuku Umar, 2020)
The objective of the present study was to evaluate the giving candlenut oil (aleurites moluccanus) in commercial feed on feed conversion ratio and feed efficiency of bileh fish (Rasbora sp.). Thecompletely randomized design method was used in this study with four treatments and three replications. The treatments studied were pellet without the giving candlenut oil (P0), pellet with the giving candlenut oil 5%/kg of feed (P1), pellet with the giving candlenut oil 10%/kg of feed (P2) and pellet with the giving candlenut oil 15%/kg of feed (P3). Bileh fish seed stocking density was 1 individu/l with the length of 3,5-4 cm and weight of 0,61-0,86 g. The culture period of fish farming was 40 days. The ANOVA test showed that the commercial feed with the giving candlenut oil gave significant effect on feed conversion ratio, feed efficiency, specific growth rate of bileh fish (Rasbora sp.), but did not give significant effect on survival rate of bileh fish seed. The best dose to increase feed efficiency and low feed conversion ratio of bileh fish seed is pellet with the giving candlenut oil 15%/kg of feed (P3).